Potential therapeutic effects of alpha lipoic acid in memory disorders - Triggiani, Leonardo (Progress in Nutrition, 2020)
With ageing, biological processes promote a gradual loss of the ability to maintain homeostasis,leading to a progressive deterioration in the body’s biochemical and physiological functions, thereby increasingsusceptibility to disease. ALA, a low-molecular-weight dithiol with a chiral centre, is a dietary supplementthought to have potential therapeutic effects for the prevention or treatment of neurodegenerativediseases. In addition, treatment with ALA is able to regulate inflammatory cell infiltration into the centralnervous system and to down-regulate VCAM-1 and human monocyte adhesion to epithelial cells. In neurodegenerativedisease models, treatment with ALA is able to improve the function of the dopamine, serotoninand norepinephrine neurotransmitters. Scientific evidence shows that ALA possesses the ability to improvememory capacity in a number of experimental neurodegenerative disease models and in age-related cognitivedecline in rodents. Studies have shown that this substance is able to reduce memory loss